The Effectiveness of Gangway Safety Net Installation on MT. Harmony Chemist While Berthing - Ardian Yahya, Reza; Djari, Janny Adriani; Indriyani, Kristin Anita (Politeknik Ilmu Pelayaran Semarang, 2025)
Abstrak: Work safety on board ships is a fundamental aspect in supporting smooth shipping operations. This study aims to identify the factors causing the suboptimal installation of gangway safety nets on the MT. Harmony Chemist ship when docked, analyze the impact caused, and formulate improvement strategies in accordance with international safety standards. A descriptive qualitative approach was used with data collection techniques through observation, interviews with key crew members including the Officer, Second Officer, and Bosun, and supported by documentation analysis. Data analysis was conducted using the Root Cause Analysis (RCA) method and the 5 Why approach, as well as problem ranking using the USG (Urgency, Seriousness, Growth) method. The research results indicate that the primary causes of suboptimal installation of gangway safety nets are the failure to conduct equipment suitability checks prior to use, the absence of a clear marking system, and weak communication among deck crew members. These conditions have implications for increased workplace accident risks, operational obstacles, and warnings from Port State Control (PSC) authorities. The USG analysis identified ineffective communication as the highest priority factor that needs to be improved. Recommendations for improvement include strengthening the communication system, conducting regular safety meetings, labeling damaged equipment, implementing double-check procedures, and conducting periodic inspections in accordance with the ISM Code and ISGOTT standards. This study underscores the importance of fully implementing a safety culture to achieve safe, professional, and internationally compliant ship operations.